A rare case of streptococcus mitis infective endocarditis complicated by heart failure in a lactating mother with recurrent breast engorgement - Mohammad Sallehuddin, Hakimah; Zakariah, Siti Zulaikha; Inche Mat, Liyana Najwa; Wan Zukiman, Wan Zul Haikal Hafiz; Hoo, Fan Kee; Ming, Tan Wei (Academy of Family Physicians of Malaysia, 2019)
Infective endocarditis during breastfeeding is rare. To the best of the authors’ knowledge, this is the second recorded case of infective endocarditis in a lactating mother. It is known that women of child-bearing age are susceptible to infective endocarditis during pregnancy when the immune system is compromised. Nevertheless, past cases were also exposed to a systemic infection via milk infected by their infant's oral commensal. Streptococcus mitis (S.Mitis) endocarditis in pregnancy has also been reported, whereby a lady delivered via caesarean section and underwent mitral valve reconstruction and annuloplasty. S. mitis is considered a pioneer streptococci commensal in human oral mucosa, appearing as early as 1-3 days after delivery. As a child grows, their oral mucosa will be colonized by more viridans streptococci, including the teeth, oropharynx and nasopharynx. In a mother who breastfeeds, a crack in the nipple and breast engorgement can be predisposing factors for systemic infection stemming from an infant's oral commensal. Both cases of breastfeeding-related infective endocarditis caused by pioneer streptococcus viridans, S.mitis in our report and S.salivarius3 in the previous report, affected the left-sided valves.